(untitled) (Applied Biological Research, 2023)
Iron deficiency anemia (IDA) affects about 20-30% of adults worldwide. The present study was aimed to determine the relationship between ischemia-modified albumin (IMA) and dynamic thiol/disulfide balance in female patients with IDA, and to reveal its effects on the development of anemia and the organism. The study included a total of 88 individuals (48 patients/ 40 healthy). IMA levels and disulfide/thiol homeostasis were measured by colorimetric and spectrophotometric methods. Total thiol (TTL) levels were found significantly positively correlated with native thiol (NTL) values (r = 0.326, p<0.05). A strong positive correlation was found between TTL and disulfide (r = 0.511, p<0.01). A negative correlation was observed between NTL and disulfide (r = -0.546, p<0.05) and between TTL and IMA (r = -0.160, p>0.05); but weak negative correlation was found between NTL and IMA (r = -0.011, p<0.05) and between IMA and disulfide (r = -0.035, p<0.05). The progression of this iron deficiency anemia is a risk factor for the occurrence of many diseases. Therefore, it is important to evaluate the parameters together in relation to the prognosis of hypoxic state and oxidant balance caused by anemia.